Serological patterns of brucellosis, leptospirosis and Q fever in Bos indicus cattle in Cameroon - Scolamacchia, F.; Handel, Ian G.; Fèvre, Eric M.; Morgan, K.L.; Tanya, V.N.; Bronsvoort, B.M. de C. (Public Library of Science, 2010)
Brucellosis, leptospirosis and Q fever are important infections of livestock causing a range of clinical conditions including abortions and reduced fertility. In addition, they are all important zoonotic infections infecting those who work with livestock and those who consume livestock related products such as milk, producing non-specific symptoms including fever, that are often misdiagnosed and that can lead to severe chronic disease. This study used banked sera from the Adamawa Region of Cameroon to investigate the seroprevalences and distributions of seropositive animals and herds. A classical statistical and a multi-level prevalence modelling approach were compared. The unbiased estimates were 20% of herds were seropositive for Brucella spp. compared to 95% for Leptospira spp. and 68% for Q fever. The within-herd seroprevalences were 16%, 35% and 39% respectively. There was statistical evidence of clustering of seropositive brucellosis and Q fever herds. The modelling approach has the major advantage that estimates of seroprevalence can be adjusted for the sensitivity and specificity of the diagnostic test used and the multi-level structure of the sampling. The study found a low seroprevalence of brucellosis in the Adamawa Region compared to a high proportion of leptospirosis and Q fever seropositive herds. This represents a high risk to the human population as well as potentially having a major impact on animal health and productivity in the region.